Complementarities between IT and Organizational Structure: The Role of Corporate Exploration and Exploitation - Ferdinand Mahr; Tobias Kretschmer (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2010)
The decentralization of organizational decision authority has been shown to be complementary to Information Technology (IT) in prior research. We draw from the information processing view of organizations, the IT and de/centralization debate, and organizational learning theory to argue that IT payoffs can also be improved by greater centralization of decision authority, contingent on a firm's corporate learning type. We argue that an exploratory learning type is best pursued with a decentralized organization design, while an exploitative learning type requires a centralized organization design. We hypothesize that under corporate exploration, IT payoffs are enhanced through greater decentralization, whereas under corporate exploitation, returns to IT are improved by greater centralization. Our study uses a novel multi-source panel on the IT capital, the degree of de/centralization, and the performance of almost 260 German manufacturing firms. We estimate production functions to assess the contribution of combning IT with de/centralization to firmlevel productivity under different corporate learning types. Our results strongly support our hypotheses and hold up to a variety of robustness tests.
urn:nbn:de:bvb:19-epub-11507-5
Keywords: 650; Lernende Organisation; Betriebliches Informationssystem; Erfolgsfaktor; Organisationsstruktur; Theorie